Bulaq - Tra le Rovine di una Rivoluzione incompiuta - Lucchini, Fabio; Morandini, Davide (Italy, 2011)
On the 25th of January 2011, thousands of Egyptians gathered in Cairo’s Tahrir Square beginning what we call now the Egyptian Revolution. Only a few hundred meters from the square, the people of the popular neighborhood Bulaq Abu el-Ela joined the protesters, finding more than a glimmer of hope in the demonstrations. Through their voices, “Bulaq” portrays their struggle against social marginalization, a movement whose destiny seems to be intertwined with that of the Egyptian spring.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films